Changing patterns of consumerism : the rise and rise of the second hand : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Visual and Material Culture at Massey University, Wellington, New Zealand - Noon, Deborah Jan (Massey University, 2011)
The aim of this thesis is to investigate the popularity of the second hand. In the wake of the conspicuous consumption which dominates the western world, where everything is new and available en masse, it seems to constitute a paradox. With the vast array of choice the consumer has today, the question of why the material culture of the second-‐hand market is so popular is intriguing. In this New Zealand study a two part approach was undertaken to answer this question. Firstly, interviews with both buyers and vendors of the second hand were conducted. Thirteen people in total were interviewed, six of whom were avid purchasers of the second hand and seven who were vendors of the second hand. Secondly, the voluminous popular literature was reviewed. This thesis takes a broader more holistic approach, rather than focusing on one particular aspect of second-‐hand consumption, as has been the predominant case thus far in international studies. Because of this broader approach, four key categories were developed to make sense of and, frame the analysis of the research findings: the ‘aesthetic’, ‘values’, ‘practices’ and ‘identity’. Each was conceptually broad but each also allowed for a particular line of enquiry within the broader field of inquiry. Within the aesthetic category, the influence of lifestyle, style and fashion on second-‐hand consumption was a focal point. This study identified the second-‐ hand market as an important vehicle of inclusion, especially in light of the current fashion for vintage clothing and retro goods. Within the values category, the concept of ethical consumption and the second hand was explored. My respondents did not give ethical consumption as a primary consideration for the choice to purchase second-‐hand goods. In contrast to iii the growing literature on ethical consumption, this study found greater consideration was given to a moral obligation to give back and the enactment of a conscience of care in second-‐hand consumption. The concept of thrift and other hedonistic motivations were the focus of the practices category. Thrift has been given little consideration in the literature yet was found to be very influential in respondent’s choices especially in today’s economic uncertainty. Of the more hedonistic motivations the findings echoed much of the conclusions identified in earlier literature on the second hand. The final category of research was identity. Reinforcing the existing academic literature, the importance of defining oneself and place in the world was found to be paramount. Differentiation and uniqueness were most valued and the second-‐hand market was privileged as the best source of goods with which to express one’s identity. The overall findings of this study endorse and also qualify the current academic literature on the second hand. Given the small sample size in this research, it is hoped that this study will act as a stimulus to further research.
Keywords: Second-hand trade; Second-hand shopping; Ethical consumption; Consumer preference